Dual-energy CT of liver metastases in patients with uveal melanoma - Jens Altenbernd; Axel Wetter; Michael Forsting; Lale Umutlu (European Journal of Radiology Open, 2016)
Objective: To investigate the value of different kVp images of dual-energy CT (DECT) for the detection of liver metastases. Methods: 20 Patients with uveal melanoma were investigated with DECT of the liver. In each patient contrast-enhanced DECT imaging with arterial delay was performed. Number and size of metastases were documented on arterial phase 80-kVp images, virtual 120-kVp images and following angiographic images (DSA) as part of hepatic chemoperfusion. Attenuation of metastases and several anatomic regions, subjective (image noise, image quality) and objective (SNR, CNR) parameters were documented. Results: The mean number of liver metastases detected was significant higher on 80-kVp images than on virtual 120-kVp/DSA images (5.6 ± 2.1 vs. 4.1 ± 1.8/4.3 ± 1.6); (p < 0.001). All lesions sizes were significant better detected with 80 kVp images than with virtual 120 kVp and DSA-Images (80 kVp vs. 120 kVp: <10 mm: 34 vs. 19, p < 0.05; 10–20 mm:, 33 vs. 25, p < 0.05; >20 mm: 56 vs. 42, p < 0.05/80 kVp vs. DSA: <10 mm: 34 vs. 18 p < 0.05; 10–20 mm: 33 vs. 24, p < 0.05; >20 mm: 56 vs. 41, p < 0.05). Number of detected small lesions <10 mm with 120 kVp compared to DSA-images were significant higher (19 vs. 13; p < 0.05), lesions 10–20 mm and >20 mm were measured statistically equally. Noise, SNR and CNR of 80 kVp images were higher compared to 120 kVp images. Image quality of 120 kVp images was higher compared to 80 kVp images. Conclusion: Low-kVp images of DECT datasets are more sensitive in detecting liver metastases of patients with uveal melanoma than virtual 120 kVp- and DSA images. Keywords: Dual energy CT, Liver, Uveal melanoma, Angiography, Staging